Role-playing Techniques to Improve Intercultural Communication Competence - Putu Ari Dharmayanti; Wayan Eka Paramartha; Luh Putu Sri Lestari; Halida Halida; Farhana Nabila Fakaruddin (Journal of Innovation in Educational and Cultural Research, 2025)
Students' inability to recognize cultural diversity can lead to violence and social gaps. If intercultural communication issues in schools persist, they may harm students' social development. Counseling teachers play a crucial role in fostering intercultural communication skills through role play technique that reinforce students to interact effectively with individuals from diverse cultural backgrounds. This study aims to see the effectiveness of role-playing techniques in improving intercultural communication of tourism vocational school students between before and after the intervention was given and after 3 weeks the role-playing technique intervention was stopped. This research is quasi-experimental research with a pre-post group design. The sampling technique is purposive sampling. The data collected in this research was then analyzed using the non-parametric Wilcoxon test. The results of this study show that there are differences in students' intercultural communication between before and after the intervention. It is hoped that the results of this research can add references in implementing role playing techniques in counseling guidance services.